Assessment of risk factors of serious diseases in OECD countries - Jindrová, Pavla; Kopecká, Lucie (Foundation of the Cracow University of Economics, 2017)
Despite a remarkable progress in health status and life expectancy in OECD countries over the past decades, there remain large inequalities across countries and also across population groups within each country. These inequalities in health status are linked to many factors, including differences in exposure to risk factors to health and in access to health care. The online OECD Health Database 2016 offers the most comprehensive source of comparable statistics on health and health systems across OECD countries. It is an essential tool to carry out comparative analyses and draw conclusion from international comparisons of health care results. The aim of this article is to use the mentioned database and apply appropriate multidimensional statistical methods to assess the risk factors in relation to mortality caused by selected serious diseases, and quantify the impact of factors such as gender, age, income inequality, costs of treatment and selected characteristics of health systems in OECD countries.
Posouzení rizikových faktorů závažných onemocnění v zemích OECD
Keywords: Comparisons; factor analysis; multidimensional comparative analysis; risk factors; serious diseases.; Porovnávání; faktorová analýza; vícerozměrné metody porovnávání; rizikové faktory; závažná onemocnění.